Conversion of E4 (E4=P4, As4, AsP3) by Ni(0) and Ni(I) Synthons – A Comparative Study. Issue 72 (23rd November 2021) - Haimerl, Maria; Graßl, Christian; Seidl, Michael; Piesch, Martin; Scheer, Manfred
Abstract: The reactivity of white phosphorus and yellow arsenic towards two different nickel nacnac complexes is investigated. The nickel complexes [(L 1 Ni)2 tol] (1, L 1 =[{N(C6 H3 i Pr2 ‐2, 6)C(Me)}2 CH] − ) and [K2 ][(L 1 Ni)2 (μ, η 1 : 1 ‐N2 )] (6 ) were reacted with P4, As4 and the interpnictogen compound AsP3, respectively, yielding the homobimetallic complexes [(L 1 Ni)2 (μ‐η 2, κ 1 :η 2, κ 1 ‐E4 )] (E=P (2 a ), As (2 b ), AsP3 (2 c )), [(L 1 Ni)2 (μ, η 3 : 3 ‐E3 )] (E=P (3 a ), As (3 b )) and [K@18‐c‐6(thf)2 ][L 1 Ni(η 1 : 1 ‐E4 )] (E=P (7 a ), As (7 b )), respectively. Heating of 2 a, 2 b or 2 c also leads to the formation of 3 a or 3 b . Furthermore, the reactivity of these compounds towards reduction agents was investigated, leading to [K2 ][(L 1 Ni)2 (μ, η 2 : 2 ‐P4 )] (4 ) and [K@18‐c‐6(thf)3 ][(L 1 Ni)2 (μ, η 3 : 3 ‐E3 )] (E=P (5 a ), As (5 b )), respectively. Compound 4 shows an unusual planarization of the initial Ni2 P4 ‐prism. All products were comprehensively characterized by crystallographic and spectroscopic methods. Abstract : The reaction of [(NacnacNi)2 tol] with white phosphorus, yellow arsenic and the interpnictogen compound AsP3 leads in dependence of the temperature to different complexes ([(NacnacNi)2 (μ‐η 2, κ 1 :η 2, κ 1 ‐E4 )] and the paramagnetic [(NacnacNi)2 (μ, η 3 : 3 ‐E3 )] (E=P, As)). The reduction was performed with KC8 and leads to similar but also different structured products. Thus, a large variety of different polypnictogen units are formed coordinated by nickel nacnac complexes.